Gait Speed as a Guide for Blood Pressure Targets in Older Adults: A Modeling Study. Issue 5 (May 2016) - Odden, Michelle C.; Moran, Andrew E.; Coxson, Pamela G.; Peralta, Carmen A.; Goldman, Lee; Bibbins‐Domingo, Kirsten
Abstract : Objectives: To evaluate the potential for gait speed to inform decisions regarding optimal systolic blood pressure targets in older adults. Design: Forecasting study from 2014 to 2023 using the Cardiovascular Disease Policy Model, a Markov model. Setting: National Health and Nutrition Examination Survey. Participants: U.S. adults aged 60–94 stratified into fast walking, slow walking, and poor functioning (noncompleters) based on measured gait speed. Measurements: Lowering SBP to a target of 140 or 150 mmHg was modeled in persons with (secondary prevention) and without (primary prevention) a history of coronary heart disease or stroke. Based on clinical trials and observational studies, it was projected that slow‐walking and poor‐functioning participants would have greater noncardiovascular mortality. Myocardial infarctions (MIs), strokes, deaths, cost, and disability‐adjusted life years (DALYs) were measured. Results: Regardless of gait speed, it was projected that secondary prevention to a systolic blood pressure (SBP) of 140 mmHg would prevent more events and save more money than secondary prevention to 150 mmHg. Similarly, primary prevention to 140 mmHg in fast‐walking adults was projected to prevent events and save money. In slow‐walking adults, primary prevention to 150 mmHg was projected to prevent MIs and strokes and save DALYs but was cost saving only in men; intensification to 140 mmHg is of uncertain benefit in slow‐walking individuals. Primary prevention in poor‐functioning adults to a target of 140 or 150 mmHg SBP is projected to decrease DALYs. Conclusion: The most cost‐effective SBP target varies according to history of cardiovascular disease and gait speed in persons aged 60–94. These projections highlight the need for better estimates of the benefits and harms of antihypertensive medications in a diverse group of older adults, because the net benefit is sensitive to the characteristics of the population treated.